PENAMPILAN RANDOM AMPLIFIED POLYMORPHIC DNA PADA Azadirachta indica A. Juss DARI TAMAN NASIONAL BALURAN - Ahmad, Fajarudin; Poerba, Yuyu S. (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Azadirachta indica A. Juss (Apocynaceae) is a large tree of the lowland tropical rainÃ‚Â forest of Southeast Asia that occurs in Thailand, the Malay Peninsula, on the island ofÃ‚Â Java (East Java) and Lesser Sunda Islands. Its economic value was in its wood (timber),Ã‚Â and as medicinal plant. The information on genetic diversity of the species is very limited.Ã‚Â Hence studies were initiated and genetic diversity estimated using RAPD markers inÃ‚Â 27 accessions of A.indica procured from three geographical regions of TN Baluran andÃ‚Â Balai Litbang Kehutanan. Seven selected Operon primers (10 mer) generated a totalÃ‚Â of 133 consistent amplification products ranging from 132 bp to 5.6 Kb. The clusterÃ‚Â analysis separated the 27 individuals into 2 clusters. The range of genetic dissimilarityvalue among samples was from 0.07 to 0.33, while genetic distance among populationsÃ‚Â was from 0.04 to 0.10. These values showed that A. indica from TN Baluran was notÃ‚Â genetically diverse population.Ã‚Â Key words: Azadirachta indica, genetic diversity, RAPD